State Expenditure or Political Agenda? A Critical Analysis of APBN Priorities at the Onset of a New Government - Mardianto, Rahmad; Destiana, Rega; Indriyani, Rivani; Putri, Shabilla Risty Eka; Mardiani, Tri; Wahyuningsih, Wahyuningsih; Nuraya, Ahmad Setiawan (Santoso Academy Network, 2025)
This study analyzes spending priorities in the 2025 State Budget at the outset of the new government in Indonesia, aiming to evaluate whether budget allocations truly reflect the long-term needs of society or are predominantly influenced by short-term political interests. A primary concern is the potential for budget deviations to be utilized as a means of enhancing political image, advancing populist initiatives, or rewarding political allies. The research employs a mixed-methods approach, integrating quantitative analysis of State Budget data and welfare indicators with qualitative analysis of policy narratives and public opinion. The findings reveal that the infrastructure and social assistance sectors have seen significant budget increases, particularly in areas that benefit the ruling government. In contrast, the education and environmental sectors received comparatively less attention. This pattern suggests a political spending approach that is not fully aligned with national development planning documents. The implication is that the State Budget risks becoming a political tool rather than a genuine instrument of development. The originality of this study lies in its focus on the onset of a new government period, employing a combination of analytical and critical approaches to uncover the tendencies toward the politicization of the state budget.